Neural Matrix and Its Role in Preoperative Evaluation of Partial Epilepsy. Issue 4 (December 2017) - Wu, Jingzhan; Zhou, Mingming
The network characteristic of the central neural system has been widely accepted as a basic fabric form. However, the matrix characteristics of neural network are still not fully understood. If we ignore the matrix characteristics of the neural networks and just pay close attention to its connection mode, we are likely to fall into the theory of mechanical reductionism. This can lead to a problem in representing consciousness in a disadvantageous situation. It can also be a barrier to further improving the global workspace theory. Incomplete elucidation of the mechanisms of consciousness representation can also affect the assessment of the surgical outcome of partial epilepsy with conscious injury. Therefore, this paper reviews the epistemological development of neuroscience. We will initially describe the matrix characteristics of the neural system and their significance to the information processing mechanism, and further explore the role of neural matrix in identifying cases of partial epilepsy with little effect on the resection of the lesion.